High Sensitivity of Endoscopic Ultrasound-Guided Fine-Needle Aspiration and Endoscopic Ultrasound-Guided Fine-Needle Biopsy in Lymphadenopathy Caused by Metastatic Disease: A Prospective Comparative Study - Per Hedenström; Vasilis Chatzikyriakos; Roozbeh Shams; Catarina Lewerin; Riadh Sadik (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The diagnostic work-up of lymphadenopathy is challenging but important to determine the correct therapy. Nevertheless, few studies have addressed the topic of endosonography (EUS)-guided tissue acquisition in lymphadenopathy. Therefore, we aimed to evaluate the accuracy and safety of EUS-guided fine-needle biopsy sampling (EUS-FNB) in intrathoracic and intraabdominal lymphadenopathy. Methods In a tertiary care center, patients with lymphadenopathy referred for EUS-guided sampling were included prospectively from 2014 to 2019 (NCT02360839). In all cases, EUS-FNB (22 gauge) and EUS-guided fine-needle aspiration (EUS-FNA) (25 gauge) were performed. The patients were randomized to the first needle pass with FNB or FNA. Study outcomes were the diagnostic accuracy and adverse event rate. Results Forty-eight patients were included (median age: 69 years [interquartile range, 59-76]; 24/48 females [50%]). The final diagnoses were metastasis (n=17), lymphoma (n=11), sarcoidosis (n=6), and inflammatory disease (n=14). The diagnostic performance of the two modalities was comparable, including a high sensitivity for metastatic nodes (EUS-FNB: 87% vs. EUS-FNA: 100%, p=0.5). The sensitivity for lymphoma was borderline superior in favor of EUS-FNB (EUS-FNB: 55% vs. EUS-FNA: 9%, p=0.06). No adverse events were recorded. Conclusions In lymphadenopathy, both EUS-FNB and EUS-FNA are safe and highly sensitive for metastatic lymph node detection. Lymphoma diagnosis is challenging regardless of the needle used.